Understanding citizen’s intention to use mobile government services in Bangladesh: role of perceived good governance and less corruption - Sultana, Mst Rebeka; Ahlan, Abdul Rahman (2014)
This study aims to understand the factors influencing the citizen’s intention to use Mobile Government services by using the UTAUT as a based theoretical model. Citizen’s perceived good governance and less corruption is considered as an additional factor that influences their intention to use m-government services. Data relating to constructs were collected from 524 citizens in Bangladesh. Structural Equation Modeling (SEM) analysis was conducted to test the model. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were performed to examine the construct validity, convergent validity and goodness of fit of structural models and measurement models. The hypothesized structural model fits the data well. The results show that the significant factors that lead to the adoption of mobile government are perceived good governance and less corruption and performance expectancy however, effort expectancy and social influence are not significant towards the intention to use mobile government.